Book Review: Handbook of geotourism, by Ross Dowling and David Newsome (Eds.), 2018. Edward Elgar Publishing Limited, Cheltenham, UK. 520 pages. Hardback: price £190, ISBN: 9781785368851. - Duszyński, Filip (Geologos, 2021)
Book Review: Handbook of geotourism, by Ross Dowling and David Newsome (Eds.), 2018. Edward Elgar Publishing Limited, Cheltenham, UK. 520 pages. Hardback: price £190, ISBN: 9781785368851.